2019
DOI: 10.1002/nbm.4181
|View full text |Cite
|
Sign up to set email alerts
|

Combined endogenous MR biomarkers to assess changes in tumor oxygenation induced by an allosteric effector of hemoglobin

Abstract: Hypoxia is a crucial factor in cancer therapy, determining prognosis and the effectiveness of treatment. Although efforts are being made to develop methods for assessing tumor hypoxia, no markers of hypoxia are currently used in routine clinical practice. Recently, we showed that the combined endogenous MR biomarkers, R1 and R2*, which are sensitive to [dissolved O2] and [dHb], respectively, were able to detect changes in tumor oxygenation induced by a hyperoxic breathing challenge. In this study, we further v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Attempts were also made to correlate R 2 * values with expression of HIF-1α: the mean R 2 * value correlated moderately with the level of HIF-1α in breast invasive ductal carcinoma (Liu et al, 2013), in human glioma (Tóth et al, 2013), but no correlation was found in renal carcinoma (Li et al, 2015). Using pharmacological manipulation of tumor oxygenation, it was found that the evolution of R 2 * was consistent with changes in tumor oxygenation after isosorbide dinitrate administration (Jordan et al, 2000) and the hemoglobin modifier ITTP (Cao-Pham et al, 2020). For the latter, the increase in R 2 * resulted from an increase in oxygen release from blood, inducing an increase in [dHb] (Cao-Pham et al, 2020).…”
Section: Magnetic Resonance Imagingusing Endogenous Contrastmentioning
confidence: 88%
See 4 more Smart Citations
“…Attempts were also made to correlate R 2 * values with expression of HIF-1α: the mean R 2 * value correlated moderately with the level of HIF-1α in breast invasive ductal carcinoma (Liu et al, 2013), in human glioma (Tóth et al, 2013), but no correlation was found in renal carcinoma (Li et al, 2015). Using pharmacological manipulation of tumor oxygenation, it was found that the evolution of R 2 * was consistent with changes in tumor oxygenation after isosorbide dinitrate administration (Jordan et al, 2000) and the hemoglobin modifier ITTP (Cao-Pham et al, 2020). For the latter, the increase in R 2 * resulted from an increase in oxygen release from blood, inducing an increase in [dHb] (Cao-Pham et al, 2020).…”
Section: Magnetic Resonance Imagingusing Endogenous Contrastmentioning
confidence: 88%
“…Using pharmacological manipulation of tumor oxygenation, it was found that the evolution of R 2 * was consistent with changes in tumor oxygenation after isosorbide dinitrate administration (Jordan et al, 2000) and the hemoglobin modifier ITTP (Cao-Pham et al, 2020). For the latter, the increase in R 2 * resulted from an increase in oxygen release from blood, inducing an increase in [dHb] (Cao-Pham et al, 2020). However, the evolution of R 2 * was not predictive of evolution of tumor oxygenation (as measured by EPR oximetry) after administration of inhibitors of oxygen consumption (insulin and AINS) (Jordan et al, 2006b) or after the RSR13 hemolobin modifier (Hou et al, 2004).…”
Section: Magnetic Resonance Imagingusing Endogenous Contrastmentioning
confidence: 94%
See 3 more Smart Citations